DAMPAK KEBIJAKAN PENDIDIKAN IPAS TERHADAP KESETARAAN GENDER DI SEKOLAH MADRASAH IBTIDAIYAH - Syahrul Rahmansyah (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2024)
Natural and Social Sciences Education (IPAS) plays a crucial role in the curriculum of Madrasah Ibtidaiyah Kecamatan tenayan Raya Kota Pekanbaru by providing a comprehensive understanding of natural, social, and gender equality aspects. This study aims to analyze the impact of IPAS policies on gender equality at the primary education level through a qualitative approach with in-depth interview techniques, direct observation, and document analysis related to IPAS policies, textbooks, and the implementation of classroom learning. The results showed that 72% of students began to understand the concept of gender equality after participating in IPAS learning, while 65% of teachers have implemented more gender-inclusive teaching methods. However, it is still found that 60% of teaching materials contain gender bias, and 70% of teachers have not received formal training on gender perspectives. Cultural and social factors are also a significant challenge, with 64% of students coming from environments that still maintain traditional gender norms. Therefore, this study recommends the need for intensive training for teachers, revision of the IPAS curriculum to be more gender-inclusive, and support from parents and the community to create a more equal learning environment. With these efforts, the IPAS policy is expected to be more effective in instilling gender equality values from an early age in Madrasah Ibtidaiyah